2011
DOI: 10.1073/pnas.1110144108
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil transmigration triggers repair of the lung epithelium via β-catenin signaling

Abstract: Injury to the epithelium is integral to the pathogenesis of many inflammatory lung diseases, and epithelial repair is a critical determinant of clinical outcome. However, the signaling pathways regulating such repair are incompletely understood. We used in vitro and in vivo models to define these pathways. Human neutrophils were induced to transmigrate across monolayers of human lung epithelial cells in the physiological basolateral-to-apical direction. This allowed study of the neutrophil contribution not onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
153
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(156 citation statements)
references
References 35 publications
2
153
1
Order By: Relevance
“…Thus, these four nutrient transporters likely originate from other neutrophil compartments that are also subject to membrane mobilization. Rather than exocytosis processes per se, it is more likely that transepithelial migration, a process that induces strong signaling loops in migratory neutrophils and the surrounding tissue (48)(49)(50) and that was not reproduced in our in vitro activation assay, played a role in the induction of nutrient transporter surface expression. Consistently, in vitro incubation of blood neutrophils with CF airway fluid does not fully recapitulate this process.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these four nutrient transporters likely originate from other neutrophil compartments that are also subject to membrane mobilization. Rather than exocytosis processes per se, it is more likely that transepithelial migration, a process that induces strong signaling loops in migratory neutrophils and the surrounding tissue (48)(49)(50) and that was not reproduced in our in vitro activation assay, played a role in the induction of nutrient transporter surface expression. Consistently, in vitro incubation of blood neutrophils with CF airway fluid does not fully recapitulate this process.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the mucosa revealed that each of the CK subunits is expressed in cultured intestinal epithelial cell lines, murine colonic epithelia, and in human colonic epithelia (37).During periods of high energy demand, the phosphocreatine pool and CK work to maintain constant concentrations of ATP and ADP. As such, CK functions as a buffer for cytosolic phosphorylation potential that appears to be critical for the proper functioning of a variety of cellular ATPases β-Catenin signaling through T cell factor/lymphoid enhancer factor (TCF/LEF) transcription factors plays a notable role within AJs and in barrier regulation during active mucosal inflammation (31). Studies derived from microarray analysis of pulmonary epithelial cells following neutrophil (polymorphonuclear leukocyte [PMN]) transmigration revealed epithelial gene programming that results in activated β-catenin signaling and the restoration of epithelial barrier function (31).…”
Section: Molecular Aspects Of Barrier Regulation In the Mucosamentioning
confidence: 99%
“…Of note, this method was originally championed by two nephrologists, Schwartz and Kassirer, in the 1970s 11 but has not been commonly used in the nephrology literature other than by the decision analysis disciples at Tufts University. It is a useful method to quantify outcomes and costs of various diagnostic and therapeutic choices under many variables.…”
Section: Disclosurementioning
confidence: 99%
“…First, mediators of renal fibrosis often exert a bifunctional role (i.e., they promote chronic damage but at the same time they are essential in renal epithelial repair). Thus, renal tubular and lung epithelial repair is delayed following acute injury if b-catenin is blocked, 11,12 and, conversely, overexpression of Wnt-4 and b-catenin promoted the proliferation of renal tubular cells. 13 Thus, it is unknown what the consequence of chronic b-catenin antagonism would be in CKD if AKI is superimposed.…”
mentioning
confidence: 99%